Characterization of Captive Breeders to Preserve the Residual Genetic Diversity of Adriatic Sturgeon (Acipenser naccarii) - Federica Barca; Stefano Dalle Palle; Luca Schiavon; Chiara Samassa; Giuseppe Castaldelli; Elisa Boscari; Leonardo Congiu (Diversity, 2022)
Since 1996, the Adriatic sturgeon (Acipenser naccarii) has been inscribed on the IUCN Red List as “Critically Endangered and possibly extinct in the wild”. Nowadays, its survival totally depends on restocking programs conducted by releasing juveniles generated from adult breeders reared in aquaculture. Conducting accurate genetic characterizations of all individuals potentially involved in reproduction activities is therefore of primary importance to avoid inbreeding and to maximize the genetic diversity transmitted to following generations. Since all animals reared in captivity descend from a single stock of wild origin, this offers the ideal condition for carrying out relatedness analysis based on parentage allocations. In this study, we provided the most complete characterization of about 500 individuals representing the most diverse extant stock of Adriatic sturgeon. Through the analyses of mitochondrial d-loop and 15 microsatellite loci selected from 24 genotyped loci, we identified about 30 different familiar groups, updating data on breeding stocks, increasing the genetic information already available, and extending the analyses to animals never genotyped before. Given its completeness, it will represent a reference database for any future parental allocation of recaptured animals for the inclusion of all other stocks present, as well as for the development of a long-term breeding plan. The approach used has also been proven useful on individuals of unknown genealogy, allowing for the identification of family groups and thus being proven to be promising for the analysis of stocks of other tetraploid sturgeon species.